Policies for Sustainable Accessibility and Mobility in Urban Areas of Africa - Stucki, Martin (World Bank, Washington, DC, 2016)
This paper: Gives the reader an overview of the main accessibility and mobility issues faced by African urban areas, namely stemming from benchmark analysis among representative urban areas selected across the continent; Provides the reader with an overview of the lessons stemming from international experience over the past twenty years; and Proposes a conceptual framework and a set of policy recommendations meant to improve accessibility and mobility conditions in urban areas of Africa.